Are We Getting Better?: Ongoing Challenges of Atrioventricular Valve Repair in Children With Single Ventricle Physiology - Sachiko Kadowaki; Maelys Venet; Teerapong Tocharoenchok; Kok Hooi Yap; Chun‐Po Steve Fan; Yasmin Zahiri; Mimi X. Deng; Olivier Villemain; Alejandro Floh; David J. Barron; Osami Honjo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study aimed to assess impact of atrioventricular valve (AVV) regurgitation onset, timing of AVV repair (AVVr), ventricular morphology, and era effect on AVVr outcomes in a single ventricle population. Methods A retrospective review of 155 patients with single ventricle physiology who underwent AVVr between 1998 and 2022 was conducted. Transplant‐free survival, discharge alive, and AVV reoperation were assessed using the Kaplan–Meier survival method, stratified by the timing of AVVr (Group1 [G1], prebidirectional cavopulmonary shunt, N=33; G2, at or post‐shunt, N=93; G3, at or post‐Fontan, N=29). Cox proportional hazard models were used to assess the association of the timing of AVVr with death or transplant. Results Transplant‐free survival at 10 years was lowest in G1 (G1, 16% [95% CI, 4%–35%]; G2, 65% [95% CI, 53%–74%]; G3, 85% [95% CI, 65%–94%], P<0.001). In the multivariate analysis, AVVr prebidirectional cavopulmonary shunt was an independent risk factor for failure to be discharged alive (P<0.001) but not for overall survival (P=0.12). Meanwhile, the likelihood of discharge alive improved over the period in the entire cohort (P<0.001), and right ventricle morphology (P=0.02) and weight <5 kg (P<0.01) at AVVr were significantly associated with death. In the multistate model, persistent or recurrent AVV regurgitation and ventricular dysfunction post‐sAVVr were significantly associated with death, with hazard ratios of 3.8 (95% CI, 2.0–7.3, P<0.001) and 32 (95% CI, 13–77, P<0.001), respectively. Conclusions Patients with single ventricles who required AVVr, particularly before bidirectional cavopulmonary shunt, have poorer transplant‐free survival with no meaningful improvement over the past 2 decades. Small weight and morphologic right ventricle were strongly associated with increased mortality. Alternative treatment strategies should be considered for this high‐risk subgroup.